2019
DOI: 10.1002/poc.3991
|View full text |Cite
|
Sign up to set email alerts
|

Can aromaticity trigger thermal [1,5]‐halogen shift towards the forbidden antarafacial mode?: A density functional case study

Abstract: [1,5]‐H shift of (Z,Z) 1,3‐pentadienes are known to take suprafacial mode. The stereochemical fate of the reaction when halogens are involved in the [1,5]‐shift in similar (Z,Z) 1,3‐pentadienes is presented in this work. Interesting tendency of fluorine to take up the forbidden and relatively expensive antarafacial path as an economical route for [1,5]‐fluorine shift is owed to the aromaticity of the transition state. Remarkable correlations between various aromaticity indices (bond alternation coefficient [BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
(76 reference statements)
1
5
0
Order By: Relevance
“…A similar joint effect of acceptor (captor) and donor, also known as captodative effect, was shown to influence radical stabilities . Thus, like our previously reported superactivated Cope substrate, this polarizing substitution generates a highly activated 1,3-pentadiene that was predisposed to undergo [1,5]-hydrogen shift.…”
Section: Results and Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…A similar joint effect of acceptor (captor) and donor, also known as captodative effect, was shown to influence radical stabilities . Thus, like our previously reported superactivated Cope substrate, this polarizing substitution generates a highly activated 1,3-pentadiene that was predisposed to undergo [1,5]-hydrogen shift.…”
Section: Results and Discussionsupporting
confidence: 62%
“…F, Cl, and Br. Kalpana and Akilandeswari 54 showed that among halogens, fluorine prefers an antarafacial path whereas chlorine and bromine prefer a suprafacial shift. Although the TS for the antarafacial shift was still shown to be aromatic, 112 it is likely to be electronically different from the rest and will not be further discussed in this work.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations